Does endo-tracheal tube clamping prevent air leaks and maintain positive end-expiratory pressure during the switching of a ventilator in a patient in an intensive care unit? A bench study. - Emanuele Turbil; Nicolas Terzi; Carole Schwebel; Martin Cour; Laurent Argaud; Claude Guérin (PLoS ONE, 2020)
Objectives When patients with acute respiratory distress syndrome are moved out of an intensive care unit, the ventilator often requires changing. This procedure suppresses positive end expiratory pressure and promotes lung derecruitment. Clamping the endotracheal tube may prevent this from occurring. Whether or not such clamping maintains positive end-expiratory pressure has never been investigated. We designed a bench study to explore this further. How the study was done We used the Elysee 350 ventilator in 'volume controlled' mode with a positive end-expiratory pressure of 15 cmH2O, connected to an endotracheal tube with an 8 mm internal diameter inserted into a lung model with 40 ml/cmH2O compliance and 10 cmH2O/L/s resistance. We measured airway pressure and flow between the distal end of the endotracheal tube and the lung model. We tested a plastic, a metal, and an Extra Corporeal Membrane Oxygenation clamp, each with an oral/nasal, a nasal, and a reinforced endotracheal tube. We performed an end-expiratory hold then clamped the endotracheal tube and disconnected the ventilator. We measured the change in airway pressure and volume for 30 s following the disconnection of the ventilator. Results Airway pressure decreased thirty seconds after disconnection with all combinations of clamp and endotracheal tube. The largest fall in airway pressure (-17.486 cmH2O/s at 5 s and -18.834 cmH2O/s at 30 s) was observed with the plastic clamp combined with the reinforced endotracheal tube. The smallest decrease in airway pressure (0 cmH2O/s at 5 s and -0.163 cmH2O/s at 30 s) was observed using the Extra Corporeal Membrane Oxygenation clamp with the nasal endotracheal tube. Conclusions Only the Extra Corporeal Membrane Oxygenation clamp was efficient. Even with an Extra Corporeal Membrane Oxygenation clamp, it is important to limit the duration the ventilator is disconnected to a few seconds (ideally 5 s).